Benefits of cocoa (Theobroma cacao) fermentation in the food industryilimbi) and its Potential Agro-industrial Processes - Celi Sabando, Kristley David; Chamorro Portilla, María Cristina; Ballesteros Jerez, Jessica Guadalupe; Barrigas Revelo, Diego Alejandro (Tierra Infinita, 2024)
This study assesses the impact of different fermentation methods on the organoleptic properties and quality of cocoa beans. Three main techniques were analyzed: fermentation in jute sacks, heap fermentation, and box fermentation. Fermentation in jute sacks, though a traditional method, faces limitations in fermentation efficiency and proper drainage, often resulting in partial and heterogeneous fermentation. On the other hand, heap fermentation is commonly adopted by small producers due to its low cost and ease of implementation; however, it requires meticulous management, including regular turning, to ensure uniform fermentation and quality in the final product. In contrast, box fermentation is identified as the most controllable and effective method, significantly influencing the sensory profile of the bean through specific selection of the type of wood used. Comparative tests indicate a notable improvement in bean quality with this method, making it the preferred choice for producing high-quality chocolate. This analysis underscores the critical importance of selecting an appropriate fermentation method to optimize the sensory characteristics of cocoa and meet the quality expectations in today's chocolate market.
Keywords: cocoa fermentation; fermentation methods; sensory quality